Transpositions Aesthetico-Epistemic Operators in Artistic Research - Arlander, Annette (Orpheus Institute Series, 2018)
"New modes of epistemic relationships in artistic research Research leads to new insights rupturing the existent fabric of knowledge. Situated in the still evolving field of artistic research, this book investigates a fundamental quality of this process. Building on the lessons of deconstruction, artistic research invents new modes of epistemic relationships that include aesthetic dimensions. Under the heading transposition, seventeen artists, musicians, and theorists explain how one thing may turn into another in a spatio-temporal play of identity and difference that has the power to expand into the unknown. By connecting materially concrete positions in a way familiar to artists, this book shows how moves can be made between established positions and completely new ground. In doing so, research changes from a process that expands knowledge to one that creatively reinvents it. Contributors: Annette Arlander (University of the Arts Helsinki), Paulo de Assis (Orpheus Institute, Ghent), Rosi Braidotti (Utrecht University), Leif Dahlberg (Royal Institute of Technology Stockholm), Lucia D'Errico (Orpheus Institute, Ghent), Mika Elo (University of the Arts Helsinki), Laura González (Royal Conservatoire of Scotland), Esa Kirkkopelto (University of the Arts Helsinki), Yve Lomax (Royal College of Art, London), Cecile Malaspina (CNRS-Université Paris 1/Université Paris 7), Tor-Finn Malum Fitje (independent artist, Oslo), Dieter Mersch (Zurich University of the Arts), David Pirrò (University of Music and Performing Arts Graz), Hans-Jörg Rheinberger (Max Planck Institute for the History of Science, Berlin), Hanns Holger Rutz (University of Music and Performing Arts Graz), Michael Schwab (Orpheus Institute, Ghent/University of Applied Arts Vienna), Birk Weiberg (Zurich University of the Arts)"